(x*x)+18x+5=0

Simple and best practice solution for (x*x)+18x+5=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x*x)+18x+5=0 equation:


Simplifying
(x * x) + 18x + 5 = 0

Multiply x * x
(x2) + 18x + 5 = 0
x2 + 18x + 5 = 0

Reorder the terms:
5 + 18x + x2 = 0

Solving
5 + 18x + x2 = 0

Solving for variable 'x'.

Begin completing the square.

Move the constant term to the right:

Add '-5' to each side of the equation.
5 + 18x + -5 + x2 = 0 + -5

Reorder the terms:
5 + -5 + 18x + x2 = 0 + -5

Combine like terms: 5 + -5 = 0
0 + 18x + x2 = 0 + -5
18x + x2 = 0 + -5

Combine like terms: 0 + -5 = -5
18x + x2 = -5

The x term is 18x.  Take half its coefficient (9).
Square it (81) and add it to both sides.

Add '81' to each side of the equation.
18x + 81 + x2 = -5 + 81

Reorder the terms:
81 + 18x + x2 = -5 + 81

Combine like terms: -5 + 81 = 76
81 + 18x + x2 = 76

Factor a perfect square on the left side:
(x + 9)(x + 9) = 76

Calculate the square root of the right side: 8.717797887

Break this problem into two subproblems by setting 
(x + 9) equal to 8.717797887 and -8.717797887.

Subproblem 1

x + 9 = 8.717797887 Simplifying x + 9 = 8.717797887 Reorder the terms: 9 + x = 8.717797887 Solving 9 + x = 8.717797887 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + x = 8.717797887 + -9 Combine like terms: 9 + -9 = 0 0 + x = 8.717797887 + -9 x = 8.717797887 + -9 Combine like terms: 8.717797887 + -9 = -0.282202113 x = -0.282202113 Simplifying x = -0.282202113

Subproblem 2

x + 9 = -8.717797887 Simplifying x + 9 = -8.717797887 Reorder the terms: 9 + x = -8.717797887 Solving 9 + x = -8.717797887 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + x = -8.717797887 + -9 Combine like terms: 9 + -9 = 0 0 + x = -8.717797887 + -9 x = -8.717797887 + -9 Combine like terms: -8.717797887 + -9 = -17.717797887 x = -17.717797887 Simplifying x = -17.717797887

Solution

The solution to the problem is based on the solutions from the subproblems. x = {-0.282202113, -17.717797887}

See similar equations:

| 225-6x=30x+17 | | h=-16t^2+80t+6 | | f(x)=-0.5x^3+2.5x^2+2x-10 | | 6.4x-3.5x=-46.4 | | -5g-7=3 | | -2n-15=61 | | f(x)=x^2+5x-2(2f(2)) | | f(x)=x^2+5x-2 | | 6+10x=42 | | [2-5(6+11)]= | | -4x+9y=-27 | | -3v+32=-7v+2(1-3v) | | 5x+6y=-18 | | -7x-2y=52 | | 2x^2-2304=0 | | 3+10=80-4 | | 4x+6y=-26 | | (8x+2)-4=18 | | 331x+6=7 | | 13+5= | | 18q=-11 | | q+13=61 | | -5x+49=-8(x-8) | | 8x-110=2x-14 | | 3+2x=x-5 | | 11z^2=-18 | | s+9=37 | | 2+3m= | | b^2-4b-b+4= | | w-8=-2 | | Y=x^2+4x+8 | | 3x*(2x+5)-(x+3)*(3x-1)=1 |

Equations solver categories